2y+5y=10 7y=10 y=10/7
42+4y -12 = 13y -12 -2y 4y -13y+2y = 12 -12 -42 -7y = -42 y = 6
-6y+3 = -7y+8 -6y+7y = 8-3 y = 5
T = 3x + 7y; x = 4; y = 6T = 3x + 7y (substitute 4 for x, and 6 for y)T = 3(4) + 7(6) = 12 + 42 = 54
15x+7y = 4 5x+7y = 2 Subtract the bottom equation from the top equation to eliminate y which will leave you with: 10x = 2 Divide both sides by 10 to find the value of x: x = 2/10 = 1/5 in its lowest terms. Substitute the value of x into the original equations to find the value of y: Therefore: x = 1/5 and y = 1/7
no its not a solution
6y=5y+2y 6y=7y that does't work its unequal -
(-4, -1)
2y+3y-7y+4=16 -2y=12y=-6Check it-12-18+42+4=16-30+46=1616=16
5y+8=7y 2y=8 y=4
5y+8 = 7y-6 5y-7y = -6-8 -2y = -14 y = 7
2y - 7 + 5y = 0 Collecting like terms together, 7y - 7 = 0 or 7y = 7 So that y = 1
2y+5y=10 7y=10 y=10/7
5y explanaition 5x-5x=0, 0-2y=-2y, -2y+7y=5y
If you mean: x+7y = 39 and 3x-2y = 2 Then by substitution: x = 4 and y = 5
The ordered pair is (5, 4).
-8x -7y